Diaspora is Not Like Home a Social And Economic History of Yoruba in Kano, 1912-1999 (2008)
Yoruba migration to Kano was shaped both by social and economic reality of the British colonial rule and trajectories of the post-colonial state. In Kano, the wider opportunity for the advancement of commercial frontier attracted generations of Yoruba traders, artisans, entrepreneurs and professionals. This book articulates the historical process that led to the evolution as well as the consolidation of the Yoruba commercial diaspora in Kano. Three interconnected themes: migration, entrepreneurship and intergroup relations in a commercial diaspora were systematically pursued in this work. All through the trajectory, the book has reconstructed the historical metamorphosis of the Yoruba trading diaspora chronologically from colonial period to the post-colonial era and, by extension, part of the commercial history of modern Kano. In 1912, Yoruba commerce in Kano entered a- new phase from the socio-cultural bases already established in the pre-colonial economy. Linder the British rule, Yoruba identity in Kano was dramatically transformed to become “non-natives” or “strangers." The British used diverse measures including stereotype, criminalisation and ethnic segregation to control Yoruba migration to Kano. Resentment and criminalisation were used to segregate and exclude the Yoruba from the mainstream Kano society. In this respect.- ethnic relations were mediated by colonial encounter. Colonialism challenged the migrants’ identity and self-understanding. The r transformative effects of this challenge redefined inter-ethnic relations to produce new imbalances, crystallisation of communal identities and social cohesion. As such, inter-ethnic rivalry sustained the British rule and remained pervasive in the post-colonial context. The intriguing feature of ethnic segregation as model of state structure and development provided stimulus for diaspora identity. Despite the control measures, the groundnut export and urbanisation processes in Kano influenced the greater proportion of Yoruba migration within the framework of kinship linkages. But Yoruba traders encountered structural disadvantages in the commodity trade. Commercially, Yoruba women were among the active traders whose entrepreneurial activities linked the rural markets with the urban economy and stimulated income and distribution of Kano made goods. From 1985 and up to 1999, a downward trend was recorded in Yoruba enterprise in Kano due to economic contraction and urban crises. The methodology for this study was primarily empirical in approach: In-depth oral interviews, research visits to neighbourhoods, fact finding surveys made on individuals, organisations and institutions as data sources in an interactive manner. The emphasis on field experience and broader interviews across ethnic, occupational and gender categories facilitated the validation of data collected and interpretation ensured that the analysis was a product of communal reflections. In this study, it has been found that ethnicity was fundamental in social and economic networks through which commerce was undertaken. The overriding value of Yoruba ethnic identity in Kano was the creation of a socio-economic community that allocated productive resources in the employment of labour, capital mobilisation, entrepreneurship and social security. The recreation and reorganisation of ethnic associations were largely influenced by successful entrepreneurs who played significant leadership roles. However, social functions restricted entrepreneurial investment in commercial activities. The study has examined the survival strategy employed by the Yoruba in combating incorporation and exclusion prism that curtailed, challenged or encouraged their commercial activities. As a trading community, the Yoruba used their flexible identity, professional skills and religions (both Christianity and Islam) for commercial success. The special skills of the entrepreneurs and complimentary commercial roles of artisans had led to the transfer of technical skills, improved craft industry, urban development, stimulated income and growth of markets, and tho over increasing urban population that provided the much needed skilled labour tor tho expanding industries. Yoruba enterprise generated labour supply, provided employment and above all, contributed to the process of capital accumulation Indeed, the special skills and complementary commercial roles of the Yoruba Christians constituted an invaluable asset to their acceptance among the Muslim host community Many of the Yoruba Muslim migrant households have been complotely absorbed into the cultural and religious values of Kano. Closely connected to this, is the fact that, many of the unassimllatod younger gemmation of tho Muslim Yoruba Migrants developed a plural identity As n consequence, tho commercial diaspora produced a hybrid generation namely; the Kano Yoruba, who had a stronger sentiment for the hosl community. Empirically, the two ethnic groups (Hausa and Yoruba) still retain many of tho loan words borrowed from each other’s languages for Islamic, commercial, equestrian and sundry matters. These extensive social network and marital linkages had facilitated ethnic harmony and hospitality. A remarkable aspect of this study is the discussion on tho ambivalent Hausa and Yoruba relations namely: economic competition on one hand and cultural constraints of identity on the other hand. Yoruba commercial activities in Kano have occasioned stress and suspicion generated considerably by economic competition. Some of the riots in Kano from 1953 to 1999 were caused by socio-political problems with devastating consequences on Kano economy most especially, state of insecurity of investment, tho fear of looting, wanton destruction of lives and economic gains, and tho exodus of migrant artisans and entrepreneurs. Some of the Yoruba experienced economic dislocation. Hence, they liquidated their businesses and or relocated to their places of origin or other commercial cities in Nigeria. The study concludes that Yoruba enterprise in Kano contributed to the transmission of technical skills among different communities and the transformation of modern Kano as a commercial metropolis in Nigeria. Without family connections and support network in a competitive context, Yoruba diaspora became ethnically assertive in terms of associational life. Thus, in the process, diaspora identity restricted the prospect of integration of the migrants into the host community.